2006
DOI: 10.1200/jco.2005.03.4645
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic and Antitumor Effects of Bevacizumab in Patients With Inflammatory and Locally Advanced Breast Cancer

Abstract: Bevacizumab has inhibitory effects on VEGF receptor activation and vascular permeability, and induces apoptosis in tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
301
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 488 publications
(325 citation statements)
references
References 25 publications
19
301
1
4
Order By: Relevance
“…26 As such, there are currently several prospective studies evaluating inhibitors of angiogenesis (eg, bevacizumab) for the treatment of IBC. 27 A higher frequency of overexpression of human epidermal growth factor receptor 2 (HER2) among IBC tumors compared with non-IBC tumors has also been reported, 28,29 making HER2-directed targeted therapy with adjuvant trastuzumab important. Women In conclusion, in this large population-based study, we demonstrated that in the era of the use of anthracyclines and taxanes, survival differences between women with stage IIIB/C IBC and those with non-IBC LABC are still present, with differences observed early.…”
Section: Discussionmentioning
confidence: 99%
“…26 As such, there are currently several prospective studies evaluating inhibitors of angiogenesis (eg, bevacizumab) for the treatment of IBC. 27 A higher frequency of overexpression of human epidermal growth factor receptor 2 (HER2) among IBC tumors compared with non-IBC tumors has also been reported, 28,29 making HER2-directed targeted therapy with adjuvant trastuzumab important. Women In conclusion, in this large population-based study, we demonstrated that in the era of the use of anthracyclines and taxanes, survival differences between women with stage IIIB/C IBC and those with non-IBC LABC are still present, with differences observed early.…”
Section: Discussionmentioning
confidence: 99%
“…K trans reduction was increased following a further six cycles of bevacizumab with conventional chemotherapy. However changes in K trans did not predict response rate (RR) (Wedam et al, 2006). Several tyrosine kinase inhibitors, notably AG-013736 (Liu et al, 2005), BIBF1120 (Mross et al, 2005b) and AZD2171 (Drevs et al, 2005) have all shown dose-dependent reductions in K trans and IAUC without demonstrating clinical response.…”
Section: Biomarker Evidence Of Drug Effect -What Does It Mean?mentioning
confidence: 99%
“…In practice data are frequently suboptimal and can lead to trial data being excluded or of limited value (Eder et (Tables 1 and 2). Most were small cohort single-centre phase I trials in patients with advanced solid tumours, although a small number of phase II trials have incorporated DCE-MRI (Wedam et al, 2006). Marked variation in tumour size (Evelhoch et al, 2004), anatomy and pathophysiology and previous treatment (Morgan et al, 2003) have made data evaluation difficult and may have masked subtle drug effects, prompting a move towards stricter inclusion criteria (Morgan et al, 2003;Mross et al, 2005a;O'Dwyer et al, 2005) or using an intra-patient dose escalation design (Jayson et al, 2002;Stevenson et al, 2003).…”
Section: Data Qualitymentioning
confidence: 99%
“…The potential pleiotropic effects of anti-VEGF therapy is in part due to the fact that VEGF receptors are expressed not only on endothelial cells in tumors, but also on subsets of hematopoietic cells, stromal cells, in addition to malignant cells in certain human cancers (e.g. breast, brain, colorectal and pancreatic [11,[38][39][40]). The existing clinical data on the mechanisms of action of anti-VEGF therapy that have been suggested by preclinical studies [9,11,12] are discussed below.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%